Investigations of The Effect of Mooring Line Parameters On the Hydrodynamic Behavior of Semisubmersible Offshore Wind Turbine in Malaysia Water Environment – Physical Model Testing - Gunasegaran, Vinod Joshua (Universiti Teknologi PETRONAS, 2020)
Floating offshore wind turbines have emerged as a very reliable source of wind energy to produce electricity. Countries such as Korea and Denmark have pronounced the decision to build wind farms with offshore wind turbines. Such projects require huge budget and investments. In order to ensure project success and to avoid loss in investments, many physical model testing are conducted in order to study and evaluate the hydrodynamic behavior of the floating offshore wind turbines when subjected to various environmental loads such as wind, waves and current.